Un métier émergent en éducation : l’accompagnateur de jeunes professeurs recrutés dans le contexte d’un établissement formateur - Luc Jamet (Éducation et Socialisation)
The new outline of the teacher training program in France (Decree 19/12/2006) revolves around two main poles: « an expertise training » finalized by a Master’s and a « qualifying training » through a national competitive recruitment exam. However, the « sensitisation training » which used to promote an initial educational approach has disappeared. It is now being replaced by in-house training of young teachers whose mentors are experienced teachers from the training school. It is a new cultural space of training with all the characteristics of a cosy mental laboratory where everything is left to be created and checked from the theoretical point of view of construction of the object. Everything is to be defined within the interactions between the newly recruited and the experienced teachers, within the aims of the training course.